FAKTOR-FAKTOR YANG BERPENGARUH TERHADAP PENDAPATAN PENGRAJIN SONGKOK DI KECAMATAN GRESIK KABUPATEN GRESIK - Riskia Habiba Usman (JURNAL MANAJERIAL, 2017)
The purpose of this research is to identify the influence factors of income’s craftmen songkok in District Gresik. This research used 48 respondents as samples. Primer data were used in this research. This research tested four independent variables, namely asset, productivity, work experience and kreativity which effected dependent variable, income. This research is also to find out the effect of asset, productivity, work experience and kreativity toward income by using two-way linear regression method. The result of the research showed that asset and work experience significantly affect income, while productivity and kreativity not significantly affect income.